Quantifying six-minute walk induced gait deterioration with inertial sensors in multiple sclerosis subjects - Engelhard, Matthew M.; Dandu, Sriram Raju; Patek, Stephen D.; Lach, John C.; Goldman, Myla D. (Gait & posture, 2016)
•A sensor-based measure of gait deterioration is validated in multiple sclerosis subjects.•This measure – the Warp Score – quantifies gait cycle “stretching” induced by the six-minute walk.•Warp Scores correlate with patient-reported fatigue even after controlling for walking speed.•Measurable evidence of gait deterioration can emerge after several minutes of walking. The six-minute walk (6MW) is a common walking outcome in multiple sclerosis (MS) thought to measure fatigability in addition to overall walking disability. However, direct evidence of 6MW induced gait deterioration is limited by the difficulty of measuring qualitative changes in walking. This study aims to (1) define and validate a measure of fatigue-related gait deterioration based on data from body-worn sensors; and (2) use this measure to detect gait deterioration induced by the 6MW. Gait deterioration was assessed using the Warp Score, a measure of similarity between gait cycles based on dynamic time warping (DTW). Cycles from later minutes were compared to baseline cycles in 89 subjects with MS and 29 controls. Correlation, corrected (partial) correlation, and linear regression were used to quantify relationships to walking and fatigue outcomes. Warp Scores rose between minute 3 and minute 6 in subjects with mild and moderate disability (p<0.001). Statistically significant correlations (p<0.001) to the MS walking scale (MSWS-12), modified fatigue impact scale (MFIS) physical subscale, and cerebellar and pyramidal functional system scores (FSS) were observed even after controlling for walking speed. Regression of MSWS-12 scores on Warp Scores and walking speed explained 73.9% of response variance. Correlations to individual MSWS-12 and MFIS items strongly suggest a relationship to fatigability. The Warp Score has been validated in MS subjects as an objective measure of fatigue-related gait deterioration. Progressive changes to gait cycles induced by the 6MW often appeared in later minutes, supporting the importance of sustained walking in clinical assessment.